Interactions Between Organizational Culture, Trustworthiness, and Mechanisms for Inter-project Knowledge Sharing - Wiewiora, A.; Murphy, G.; Trigunarsyah, B.; Brown, Kerry (Jossey Bass, Ed. & Pub., 2014)
This research used a multiple-case study approach to empirically investigate the complex relationship between factors influencing inter-project knowledge sharing—trustworthiness, organizational culture, and knowledge sharing mechanisms. Adopting a competing values framework, we found evidence of patterns existing between the type of culture, on the project management unit level, and project managers’ perceptions of valuing trustworthy behaviors and the way they share knowledge, on the individual level. We also found evidence for mutually reinforcing the effect of trust and clan culture, which shape tacit knowledge sharing behaviors.